THE ROLE OF TURMERIC POWDER IN LIPID METABOLISM AND ITS EFFECT ON QUALITY OF THE FIRST QUAIL’S EGG - Saraswati, T.R.; Manalu, W.; Ekastuti, D.R.; Kusumorini, N. (Diponegoro University, 2013)
This experiment was conducted to determine the role of turmeric powder in lipid metabolism andits influence on the quality of the first quail’s egg. Sixty female quails were assigned into a completelyrandomized design with four treatments (levels of turmeric powder i.e., 0; 13.5; 27; and 54mg/quail/day) and each treatment used 15 quails. The treatment was conducted for 60 days. Parametersmeasured were proximate analysis and the quality of the first layed eggs. At the end of the experiment,serum cholesterol and triglyceride concentrations, abdominal and pectoral fat weights, and feedconsumption were measured. Chemical analysis showed that turmeric powder contained 7.97%curcumin. Supplementation of turmeric powder lowered serum cholesterol and triglycerideconcentrations, egg fat and protein contents, haugh unit and yolk index, but did not affect feed intake,abdominal and pectoral fat weights, egg weight, eggshell weight, eggshell thickness, and egg shellindex. However, quails supplemented with turmeric powder showed a variation in egg laying delayranging from 1 to 16 days. Quails supplemented with 54 mg/d turmeric powder had the highest follicleshierarchy. It was concluded that supplementation of turmeric powder with the level of 54 mg/quail/daydecreased lipid content of the egg and improved the other egg quality parameters.